Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10566-009-9090-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing the Discussion: A Commentary on “Wilderness Therapy: Ethical Considerations for Mental Health Professionals”

Abstract: Wilderness therapy programs continue to be a possible treatment modality for at-risk youth who require out-of-home care. Issues associated with wilderness therapy also continue to be a spirited topic with professionals in the field and the general public. This commentary will add additional considerations, and continue the discussion concerning wilderness therapy not addressed in the Becker (Child Youth Care Forum, doi. 10.1007/s10566-009-9085-7, 2010 this issue) article. Issues related to cost, safety of clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 9 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The secondary result is the exaggerated possibility to conclude that research results from one form of group care applies to all group care. A similar concern within the field of wilderness programs was recently articulated in this journal (Becker 2010;Scott and Duerson 2010).…”
Section: Introductionmentioning
confidence: 58%
“…The secondary result is the exaggerated possibility to conclude that research results from one form of group care applies to all group care. A similar concern within the field of wilderness programs was recently articulated in this journal (Becker 2010;Scott and Duerson 2010).…”
Section: Introductionmentioning
confidence: 58%
“…Despite the proliferation of OBH programs and the corresponding need to examine treatment outcomes, as well as the ethical difficulties associated with these types of interventions (i.e., Becker, 2010;Scott & Duerson, 2010), the empirical study of therapeutic outcomes remains limited. Prior studies have reported improvements in (a) recidivism for adjudicated youth (Castellano & Soderstrom, 1992) and sexual offenders (Lambie et al, 2000), (b) family functioning (Harper & Russell, 2008), (c) oppositional and defiant behavior among adolescents (Brand, 2001), and d) interpersonal functioning (Clark, Marmol, Cooley & Gathercoal, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 40 of the 131 (31%) programs are located in Utah, a state in which a parent may submit a non-consenting minor for treatment if a neutral and detached fact finder determines that the minor needs treatment and the non-consenting minor will not be discharged upon request if s/he continues to meet admission requirements (Lallemont, et al, 2009). Unfortunately, there are a number of noted problems with these types of programs (Friedman et al, 2006) and a lack of methodologically controlled outcome studies (Scott & Duerson, 2010; Wilson & Lipsey, 2000). In addition, the effect of this type of coercion on the parent-adolescent relationship is unknown.…”
Section: Discussionmentioning
confidence: 99%